Sustaining hope: A narrative inquiry study exploring midwives' hope‐focused practices in HIV care in Ghana - Gideon L. Puplampu; Lenora M. LeMay; Evelyn Asamoah‐Ampofo; Vera Caine (Wiley, 2023)
Abstract HIV remains a statistically significant issue for women of childbearing age in Ghana. Nurses and midwives form the backbone of care providers for the prevention of mother‐to‐child transmission programmes. However, nurses and midwives receive little support to provide the emotional aspects of HIV/AIDS care. Aim Our aim was to build an understanding of how midwives currently embrace their experience of hope and hoping to support mothers living with HIV. Design This is narrative inquiry study. Methods We engaged in two to three conversations with five midwives in rural settings in Ghana to understand their experiences of hope and hoping in their interactions with mothers living with HIV. Using the narrative inquiry common places of temporality, the social and personal, and space/place, we wrote narrative accounts for each participant and then searched for resonances across the narrative accounts. Results We highlight three emerging narrative threads that resonated across narrative accounts. The three emerging narrative threads were (1) sustaining hope by drawing on life experiences across time and place; (2) hope is sustained through a focus on relational engagement with mothers; (3) midwives embrace the possibility to learn more about hope‐focused practices. Conclusion The midwives began, although tentatively, to shine light on the things and events that diminished their abilities to maintain a hopeful perspective. At the same time, they became more comfortable and familiar with the notion of making hope visible and accessible in their experiences. Impact Since the midwives welcomed additional support to cope with the challenges they were experiencing, we imagine one day being able to make sense of how nurses and midwives engage with a narrative pedagogy of hope. Including hope‐focused practices in nursing and midwifery preservice and in‐service opportunities is important. Patient or Public Contribution There was no direct patient or public involvement in this study.